Pembuatan Pestisida Nabati Dari Isolasi Senyawa Sitronellal Pada Essential Oil Sereh Wangi (Citronella Oil) Dengan Metode Vacuum Distillation - Nazia, Cut; Ridwan, Ridwan; Aja, Cut (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
In this research, the citronellal compound contained in citronella oil was isolated using the vacuum distillation method. Citronellal is the main compound in citronella oil which plays the most role in controlling pests because it is an insect repellent (insect repellent) and antifeedant which reduces the appetite of insects and deterrents oviposition, that is, it can reduce the number of eggs produced by plant pest organisms. This is what drives the processing of citronella essential oil to be processed, by isolating the citronellal compound using vacuum distillation, with operating pressure conditions: 70 mBar, and temperature variations: 120ºC, 125ºC, 130ºC, 135ºC, 140ºC and operating time: 80,100,120,140,160 minutes. Samples were analyzed using GC-MS (Gas Chromathography Mass Spectrometry), refractive index, specific gravity and effectiveness testing in controlling pests. The research results showed that the GC-MS test results showed that the % area of citronellal before and after distillation increased by 4.59%. namely from 41.03% to 45.62%. The volume of distillate produced at each temperature increases with each variation in operating time. The maximum distillate yield was obtained at an operating temperature of 140ºC at an operating time of 160 minutes with a distillate volume of 19.7 mL. The Refractive Index value was obtained in the range 1.4472-1.4486. The density of the resulting distillate was found to be in the range 0.851-0.859. The results of testing the effectiveness of pest control show that pesticides containing citronellal compounds can prevent insects from approaching the leaves for 3 hours during the test period, and the percentage of repellency level (repellent) at 3 hours is 100%, more effective than pesticides using ordinary citronella oil. which has a repellency rate of 76.4%.